Preparedness for transplantation during COVID-19 outbreak: how to manage?. (30th September 2020) - Valdi, G; Varadi, G; Panzera, A; Parpinel, M; Peressutti, R
Abstract: Problem: When WHO declared COVID-19 "international", it was important not to damage some critical patients who need emergency procedures like organ transplantation, due to end stage organ disease. In 2003 SARS outbreak demonstrated the vulnerability of organ transplantation services o network. Descritption: If transplantation is required as a life-saving procedure, it can be conducted with appropriate risk infection assessment. It is crucial during these emergencies to assess donor pool, as it is expected to decrease. A crucial point is to organize and evaluate the surge capacity, in terms of understaffing and lack of supplies, especially in ICU. The research methods were literature review using Pub Med, CDC, ECDC, WHO, TTS, searching as key words "SARS-CoV-2", "COVID-19", "transplantation", "preparedness". The analysis has been conducted between Feb 26th 2020 and March 5th 2020. Results: As happened during SARS breakout in 2003, it is essential to establish a task force for crisis, currently updated and skilled for this particular management. Preparedness should regard especially the adoption of donor safety assessment procedures, ICU capability, the availability of covid-19 test for all the donors, and the adoption of specific post-transplant care. It is essential in this case establish preparedness in several points: education and training of the staff, practice drills, inspection of supplies, evaluation of surge capacity, relocation of patients. Lessons: SARS-CoV-2 imposed in public health to establish new protocols and guidelines, which should be regularly updated to be useful in other epidemics outbreaks or other emergency situation. These protocols should focus on donor pool and ICU capability in order to carry on transplantation activities. Key messages: This outbreak has tested the resilience of the whole system by day-by-day updating for transplantation teams and preparedness of the staff involved in transplantation management. During outbreak, seems to be useful a task force for crisis in order to support organ transplantation services.